Teachers' preparedness for transformative practice in multicultural schools: An analysis of selected post apartheid teachers' self-reports - Amosun, Olufunmilayo Ibironke (Department of Sociology, 2014)
South Africa's schooling system developed within the historical backdrop of racial subjugation of some of its citizens. The legislation of the new South African Constitution (RSA, 1996) and the South African Schools Act (DoE, 1996) overturned apartheid educational policies in order to instate a process of social justice at all levels of the South African society. Samuel (2003) notes that, teachers are shaped personally and professionally, by the context within which they developed. During apartheid most teachers were trained in mono-racial, mono-cultural schools and teacher training institutions; making them unprepared to teach in multicultural classrooms. Thus thrust into multicultural classrooms after apartheid, they were unprepared for their role. Teachers, though professionals in their field of expertise, are also positioned as role models. Therefore, their dispositions have considerable impact on learners' sense of self which eventually contributes to shaping their futures. It is therefore crucial to examine from which mindset post apartheid teachers operate and how disposed they are to fulfil the responsibility placed on them to act as agents of transformation. Hence, the study documents teachers' reports, examining their knowledge, attitude and practice to see how they have changed, how poised they are for equitable classroom practice and how resolved they are to carry out critical action for social justice. The study was carried out in Cape Town, Western Cape Province, South Africa. The study is a qualitative study that used semi-structured interviews to elicit responses from teachers working in thirteen different schools, representative of the apartheid school-types, which were selected because of their degree of racial integration at the time of data collection. The study discursively documented their notions of classroom multiculturalism1 (CM), the challenges they face, their perceived levels of change and their resolve to act as change agents for social justice. Bennett's (2003) framework for multicultural teaching provided the theoretical framework for the study. Her model, consisting of four conceptual domains, each with three dimensions 'Classroom multiculturalism' refers to the South African deracialised classrooms which was legislatively established in 1996 through a democratic process that began in 1990 and culminated in the abandonment of the apartheid laws, one of which was separate and disparate education for blacks, coloureds, Indians and whites. vi served as a guideline for exploring relevant literature that provided the guidelines for analysis. The model was rearranged and an additional concept, 'ideology of multicultural practice'2, was added to generate a new model. Using this model to investigate teachers' narratives, the study found that certain steps need to be taken at school, national, provincial, municipal council, community, and individual teacher levels for transformation of teachers' practice towards critical social justice to take to take place. The study found that most teachers felt unprepared for their role, lacking the necessary knowledge, attitude and skill for such practice. Most of them reported specific changes in their practice but some did not see why they should change. Few teachers expressed a resolve to act as critical agents of change. The study recommends the newly generated model, called 'Obligatory engagements for teachers in multicultural schools' (OETMS), as a developmental tool for teacher training for multicultural practice both at pre-service teacher training institutions and by government or private institutions, for in-service teachers. 2 'Multicultural practice' in this thesis, does not just refer to teachers' pedagogic practice, but connotes all activities in which teachers engage in, while carrying out their professional duties in multicultural schools. Cole (1989), and Steinberg and Kincheloe (2001) showed that their ideology of multiculturalism affects their multicultural practice.